Experimental membrane fouling sensors - Tan, Yi Xin. (2011)
One of the major foulants that results in formation of cake layer on ultrafiltration membrane is colloidal particles. Particle fouling greatly affects the fouling behaviours of UF membrane and therefore the membrane filtration process. The effect of particle fouling on UF membrane was investigated in this study. Experiments were carried out to look into the effect of operation parameters namely the permeate flux and feed particle concentration on the UF membrane. The model foulant chosen to represent colloidal particles in this study was bentonite.As the experiments are conducted under constant flux, the scale of membrane fouling was measured by comparing the increase in transmembrane pressure at different operating conditions. Experimental results suggest that application of higher flux and higher feed particle concentration both leads to higher transmembrane pressure. The results can be attributed to the formation of cake layer and the high fluid viscosity at high feed concentration.